2023
DOI: 10.1021/acsenergylett.2c02735
|View full text |Cite
|
Sign up to set email alerts
|

Recyclable and Ultrafast Fabrication of Zinc Oxide Interface Layer Enabling Highly Reversible Dendrite-Free Zn Anode

Abstract: The surface coating is effective in suppressing Zn dendrite and side reactions, while the existing processing methods employ complex procedures and expensive equipment. Here, we develop an I 2 -assisted processing method to in situ fabricate the ZnO interface layer on the Zn anode (denoted as IAZO). This strategy features the sustainability that the raw materials, I 2 , could be reused with a recovery ratio of 67.25% and rapid processing time that only takes 5 min. The IAZO anode achieves an extraordinary cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…The reason might be that a enough thick layer is required for such interfacial materials so that it can maintain the film integrity and ensure completely isolation of Zn from the electrolyte. [16] e.g., Zhou et al prepared a 5 μm ZnO layer by liquid-phase synthesis method to regulate Zn deposition, [13] while Du's group fabricated a 10 μm ZnO layer by I 2 -assisted processing method. [16] It is found the cycle life of Zn anode exhibited an apparent improvement along with the thickness of the ZnO layer increasing.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The reason might be that a enough thick layer is required for such interfacial materials so that it can maintain the film integrity and ensure completely isolation of Zn from the electrolyte. [16] e.g., Zhou et al prepared a 5 μm ZnO layer by liquid-phase synthesis method to regulate Zn deposition, [13] while Du's group fabricated a 10 μm ZnO layer by I 2 -assisted processing method. [16] It is found the cycle life of Zn anode exhibited an apparent improvement along with the thickness of the ZnO layer increasing.…”
Section: Introductionmentioning
confidence: 99%
“…[16] e.g., Zhou et al prepared a 5 μm ZnO layer by liquid-phase synthesis method to regulate Zn deposition, [13] while Du's group fabricated a 10 μm ZnO layer by I 2 -assisted processing method. [16] It is found the cycle life of Zn anode exhibited an apparent improvement along with the thickness of the ZnO layer increasing. Moreover, Wang et al found that only by the thickness up to 20 μm, together with the optimized crystalline surface regulation can TiO 2 interfacial layer ensure the underlayer deposition of Zn.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7] However, despite these advantages, ZIBs have not been widely commercialized, largely due to undesirable interactions between the electrolyte and Zn-metal anode, including dendritic growth on the anode surface, side reactions forming an inert passivation layer, as well as hydrogen evolution during the plating/stripping process. [8][9][10][11][12][13][14] These effects can cause poor cycling reversibility of the Zn-metal anode, leading to battery failure on the anode side.…”
mentioning
confidence: 99%